Perlindungan Hukum Terhadap Pejuang Lingkungan Hidup Dalam Mewujudkan Lingkungan Hidup Yang Baik Dan Sehat - Puspitasari, Dinarjati Eka (Jurnal Hukum & Pembangunan, 2022)
The right of environmental defenders not to be sued civilly or prosecuted criminally is part of human rights regulated in Article 66 of Law 32/2009 (UUPPLH), known as Anti Strategic Lawsuit Against Public Participation (Anti-SLAPP). But in practice, the law is used as a tool to curb public participation. In this case, environmental organizations have an important role to play in assisting communities in fighting for their environmental rights, ranging from non-judicial mechanisms to becoming amicus curiae in court. This research examines literature sources with a library research method through a statutory approach, case approach, and conceptual approach. The result indicates that although Law No. 32/2009 provides legal protection to fight for the right to a good and healthy environment, the community is still prosecuted when fighting for the right to the environment, either through a lawsuit or criminalized. In conclusion, the Anti-SLAPP regulation in Indonesia is still relatively weak in providing justice, benefits, and legal certainty for environmental fighters in Indonesia.